Comparative evaluation of antimicrobial efficacy of platelet-rich plasma, platelet-rich fibrin, and injectable platelet-rich fibrin on the standard strains of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans - Prabhdeep Kour; Pushpa S Pudakalkatti; Ancia M Vas; Swetalin Das; Sreeshma Padmanabhan (Wolters Kluwer Medknow Publications, 2018)
Context: Platelet concentrates are commonly used to promote periodontal soft- and hard-tissue regeneration. Recently, their antimicrobial efficacy is also explored. Various platelet concentrates have evolved which differ in the centrifugation protocols. Porphyromonas gingivalis (Pg) and Aggregatibacter actinomycetemcomitans (Aa) have been found to have an important role in periodontal pathology. Aims: In this study, PRP, PRF, and I-PRF are compared for their antibacterial effect against Pg and Aa. Materials and Methods: Blood samples were obtained from ten systemically and periodontally healthy individuals. Platelet concentrates were prepared using standardized centrifugation protocol. Antimicrobial activity was examined on standard strains of Pg and Aa using well diffusion method. Statistical Analysis Used: Means for the width of zones of inhibition were calculated along with standard deviations, and the comparison was made using Wilcoxon signed-rank test. Results: In case of Pg, I-PRF had the widest zone of inhibition which was significantly wider as compared to PRF. Furthermore, PRP had significantly wider zone of inhibition against PRF. In case of Aa, PRP had wider zone of inhibition which was significantly wider as compared to that of PRF and I-PRF. Conclusions: All the three platelet concentrates PRP, PRF, and I-PRF have antibacterial activity, but PRP and I-PRF are more active as compared to PRF. I-PRF being autologous and easy to prepare can be a very useful adjunct to the surgical therapy in bringing down the bacterial count helping in wound healing and regeneration.